2015
DOI: 10.1371/journal.pone.0131766
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Interval Training (HIIT) Induces Specific Changes in Respiration and Electron Leakage in the Mitochondria of Different Rat Skeletal Muscles

Abstract: High intensity interval training (HIIT) is characterized by vigorous exercise with short rest intervals. Hydrogen peroxide (H2O2) plays a key role in muscle adaptation. This study aimed to evaluate whether HIIT promotes similar H2O2 formation via O2 consumption (electron leakage) in three skeletal muscles with different twitch characteristics. Rats were assigned to two groups: sedentary (n=10) and HIIT (n=10, swimming training). We collected the tibialis anterior (TA-fast), gastrocnemius (GAST-fast/slow) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 43 publications
3
34
0
1
Order By: Relevance
“…In rats, intense exercise increased mitochondrial respiration in tibialis anterior compared to soleus (Ramos‐Filho et al . ). The specific upregulation of NDUFA9 in type II fibres may be related to the exercise employed which may recruit more type II fibres (Kristensen et al .…”
Section: Discussionmentioning
confidence: 97%
“…In rats, intense exercise increased mitochondrial respiration in tibialis anterior compared to soleus (Ramos‐Filho et al . ). The specific upregulation of NDUFA9 in type II fibres may be related to the exercise employed which may recruit more type II fibres (Kristensen et al .…”
Section: Discussionmentioning
confidence: 97%
“…The specific rate of H 2 O 2 production was determined using a linear regression curve fitted with Origin v.8.0 (OriginLab, Northampton, MA, USA). Hydrogen peroxide emission is expressed as picomoles per minute per milligram (Ramos‐Filho et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Given that mGPDH and GP are components that interlink cytosolic and mitochondrial energy transduction pathways, some physiological stimuli that could activate this pathway might also induce mGPDH/GPmediated superoxide production. A few studies have reported that high-intensity training altered mitochondrial functions in skeletal muscle [25,26], and the training augmented GP-supported mitochondrial superoxide production [26]. We recently found that hyperthermia induced GP-supported superoxide production in avian muscle mitochondria [27].…”
Section: Discussionmentioning
confidence: 88%